Effect of heterogeneous term in electrical permittivity for emulsion - Ismail, Nasser (Latakia University Journal -Basic Sciences Series, 2018)
In this research, the relation which describes the electric permittivity of emulsion was theoretically found. After that, a Matlab code was used to study the behavior of mixed permittivity changes versus the ratio between forming layer thickness around particle to its radius. We noticed from the graph that the contribution of heterogeneous term in electrical permittivity take values in the range corresponding to particle size in the range at definite value of concentration C =0.01. In addition, the contribution of heterogeneous term in electrical permittivity is proportional with the forming layer and inversely with particle radius. This study has multi-field application as: oil products, pharmacy materials, nutrients and cosmetic materials